Dynamic small-signal chirp characteristics of external and integrated modulators - Ukrit Mankong (2018)
© 2015 IEEE. We demonstrate that our recently proposed chirp measurement technique can be applied to the measurement and visualization of the small-signal dynamic chirp characteristics of modulators in vector space for the first time. Both discrete modulators and those integrated in externally modulated laser modules can be characterized by this method. The results agree with existing method to the first order approximation, whilst dynamic chirp change can also be measured during amplitude transition.